Circulation of non-polio enteroviruses in 24 EU and EEA countries between 2015 and 2017: a retrospective surveillance study. Issue 3 (March 2020) - Bubba, Laura; Broberg, Eeva K; Jasir, Aftab; Simmonds, Peter; Harvala, Heli; ,
Summary: Background: Enteroviruses can cause severe infections, especially in young children. Non-polio enterovirus infections are not notifiable in most countries in the EU and European Economic Area (EEA) region, and surveillance varies substantially between countries. We collected and analysed available enterovirus data across EU and EEA countries to assess the current epidemiological situation and need for standardising surveillance. Methods: Aggregated data on any enterovirus detected between Jan 1, 2015, and Dec 31, 2017, through national enterovirus reference laboratories were requested from representatives in all 31 EU and EEA countries. Information collected included enterovirus types detected by month, patient age group, symptom, and specimen type. We also collected sequence data on viral capsid sequences for the three most clinically relevant enterovirus types, as identified from the data. Findings: Aggregated data were provided by representatives from 24 (77%) of 31 countries. 9914 (66%) of 14 999 enterovirus infections with information about age were in children younger than 5 years, and 3197 (45%) of 7139 individuals for whom symptoms were reported had neurological symptoms. Other symptoms were non-specific fever (in 1607 [23%] patients), respiratory symptoms (in 1197 [17%] patients), hand, foot, and mouth disease (in 528 [7% patients), and myocarditis (in 39 [1%] patients). 68 deaths were temporally associated with enterovirus infection. Typing for 11 559 (67%) of 17 136 specimens revealed 66 enterovirus types. Coxsackievirus A6 was the most frequently detected enterovirus type (in 1556 [13%] of 11 559 typed enteroviruses), and 292 (65%) of 448 patients with coxsackievirus A6 infection with available clinical data presented with hand, foot, and mouth disease. Echovirus 30 was the second most frequently detected enterovirus type, representing 1412 (12%) of 11 559 typed enteroviruses, and 384 (82%) of 467 individuals with echovirus 30 infection with available clinical data had neurological symptoms. Sequences available from 18 countries showed circulation of newly emerging strains of enterovirus A71 and enterovirus D68. Interpretation: To our knowledge, this study is the largest investigation of enterovirus circulation in EU and EEA countries and confirms the availability of non-polio enterovirus data in the region. Our study highlights the wide circulation of non-polio enteroviruses in Europe, mostly affecting young children and leading to neurological symptoms. Collecting data on morbidity and mortality related to enterovirus infections, as well as harmonising case definition for surveillance, should be encouraged. Funding: None.